Analisis Angka Harapan Lama Sekolah di Indonesia Timur Menggunakan Weighted Least Squares Regression - Arifin M Kahar (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2018)
Human Development Index (HDI) is one of the data and information used by the local government to measure the achievement of human development with the basic components of quality of life that is life expectancy that represents health dimension, expected years of schooling (EYS) and mean years of schooling (MYS) represents the educational dimension, and purchasing power parity that represents decent living dimension. HDI especially in eastern Indonesia in the last three years has continued to increase but the figure is always below from the national figure even left behind if compared with West Indonesia. One dimension that is still low achievement is the educational dimension. EYS is one of the indicators on the educational dimension that is still a low achievement. Therefore, this research would like to know the influence of percentage of poor people, Gross Regional Domestic Product (GRDP) per capita, net enrollment rate (NER) of junior high school, and a ratio of educational facilities to EYS in eastern Indonesia. Using Weighted Least Squares (WLS) method concluded that the four predictor variables used were able to influence EYS in Eastern Indonesia.